Perancangan E-Catalogue Pada Akun Sosial Dan Jasa Layanan E-Commerce Pada Warung Bakso Pakdeh Di Kota Batam” - Johny Budiman; William Angelo Tio (ConCEPt - Conference on Community Engagement Project, 2021)
This community service is a descriptive service that helps MSMEs in Batam City. This service aims to provide benefits to MSME players in increasing their business again so that the MSME business can survive and compete in a new broad market, namely the online market in Batam City. This form of service is based on the sources observed by researchers. The results of this service show that (1) The importance of innovating in MSME businesses so that they can survive to compete in the broad market (2) If the availability of e-catalogs in e-commerce services on Gojek and Grab and Instagram social accounts in culinary MSME businesses at the time at this time it will be very easy to reach by the wider community in Batam City.